PENGARUH BUDAYA BIROKRASI TERHADAP EFEKTIVITAS PELAYANAN APARATUR BADAN KESATUAN BANGSA POLITIK DAN PERLINDUNGAN MASYARAKAT - MUSDAR, ANDI ZULQIFLY; PANGKEY, MASJE SILIJA; POMBENGI, JERICHO DANGA (Sam Ratulangi University, 2017)
This research describes two variables, namely bureaucratic culture and effectiveness of service apparatus. The purpose ofthis study is to determine the influence of bureaucratic culture on the effectiveness of apparatus services. Bureaucraticcultural variables were tested using 6 indicators. Variables of service effectiveness of apparatus were tested using 3dimension. This research was conducted in the office of National Unity and Political Protection Agency of Manado City.The research method used is quantitative, with data collection techniques distributing questionnaires to respondents. Thesample of this research is 41 employees of National Unity and Community Protection Agency of Manado City. The dataanalysis used is spearman rank correlation and simple linear regression using SPSS for ios. The result of spearmancorrelation coefficient correlation between bureaucracy culture and effectiveness of service apparatus is +0,467. Whichmean indicates a significant correlation. While the